A Nowcasting System for Hydrometeorological Hazard Assessment of Landslides and Flooding – Part 1: Conceptual Formulation - Abi Karam, Hugo (Anuário do Instituto de Geociências, 2024)
This study presents a novel very short-term hydro-meteorological forecasting system integrating precipitation data from Hydroestimator/NOAA. The system employs a variational version of the TopModel hydrological model alongside landslide and flood hazard models. Operating in continuous 15-minute cycles, it produces scalar and probabilistic two-dimensional hazard fields to support decision-making during extreme events across the State of Rio de Janeiro, Brazil, at a spatial resolution of 4 km. The evaluation of this system considers performance indicators based on contingency tables. Emphasizing a balanced approach between computational efficiency and product utility, this study aims to provide a robust analysis of the system's predictive capabilities in addressing hydro-meteorological challenges.